Penerapan Model AISAS dalam Komunikasi Pemasaran Digital melalui Media Sosial - Putu Chintya Dewi; Ratna Devy Winayanti (Jurnal Pustaka Komunikasi, 2026)
The development of digital technology has fundamentally transformed the landscape of marketing communication, where consumers now play a more active role in seeking information and sharing experiences through social media. Traditional consumer behavior models such as AIDA are increasingly limited in explaining the complexity of digital consumer behavior, which is more interactive and non-linear. This study aims to describe the application of the AISAS model in digital marketing communication through social media and to analyze its effectiveness compared to traditional marketing models. The research employs a systematic literature review by examining and synthesizing relevant scientific publications related to the implementation of the AISAS model on social media platforms obtained from academic databases. The findings indicate that the AISAS model, consisting of five stages (Attention, Interest, Search, Action, Share), can be optimized on different social media platforms through appropriate content strategies, information search optimization, and community engagement. The Search and Share stages emerge as key differentiating elements that reflect the characteristics of digital consumers who actively seek information and share experiences online. The implementation of AISAS has been shown to improve brand awareness, customer engagement, and conversion rates in digital marketing strategies. This study contributes to the academic literature by providing a conceptual synthesis of AISAS model applications within the social media ecosystem and highlighting its relevance as a framework for understanding digital consumer behavior in contemporary marketing communication.